Assessment of genotype x environment interactions and stability for seed yield of selected safflower (Carthamus tinctorius L.) genotypes in central and northern Sudan - Hussein, Abdalla; Ibrahim, Abu Elhassan; Hussein, Ismail; Idris, Siddig (Gezira Journal of Agricultural Science; Vol 16 No 2 (2018), 2018)
Safflower is an important oilseed crop worldwide. In Sudan, safflower is only cultivated in the Northern State along the River Nile. The success of safflower improvement and production activities can be enhanced with scientific information generated from the study of genotypes, environments and genotype by environment interactions (GEI). In this study, 15 safflower genotypes were evaluated during two consecutive winter seasons (2013/14 and 2014/15) at three locations viz Gezira, El- Suki and Hudeiba Research Station Farms of the Agricultural Research Corporation, Sudan. The objectives of this study were to estimate G x E interactions and identify the highest yielding and stable genotypes under different environments. A wide range of genetic variability was observed among the genotypes for most of the studied traits. Combined analyses of variance revealed highly significant environment, genotype and genotype x environment (GE) component of interaction and indicated wide differences among the environments and differential genotypic behavior to the tested environments. Additive main effects and multiplicative interactions (AMMI) analyses have higher efficiency in partitioning and analyzing stability studies compared to regression analysis. First and second principal component axis (PCA 1 and PCA 2) in AMMI explained 64.6% and 25.3% of the interaction sum of squares, respectively, and together they accounted for 89.9 % of the G X E sum of squares, while the regression model accounted only for 13.8% of the G X E sum of squares. Hence, AMMI analysis was superior to regression techniques in accounting for the large part of the G X E sum of squares and more effective in partitioning the interaction sum of squares. In conclusion, genotypes Saff 1, Saff 12 and Saff 14 were high yielding (582.4, 507.9 and 572.8, kg/ha, respectively) and stable under all environments. Therefore, they are recommended to be grown under winter irrigated conditions of central and northern Sudan.     يعتبر القرطم من المحاصيل الزيتية المهمة في العالم و يزرع في السودان فقط في الولاية الشمالية في المساحة الواقعة علي طول النيل. إن نجاح تحسينِ محصول القرطمِ ونشاطاتِ إنتاجِه يُمْكِنُ أَنْ يُحَسّنا بالمعلومات العلمية التي تنتج منْ دراسة التراكيب الوراثية وتفاعلاتِ البيئة والتفاعل بين التراكيب الوراثية والبيئة. قُيّمَت في هذه الدراسةِ خمسة عشرَ تركيباً وراثياً من القرطمَ علي مدي فصلي شتاء متتاليينِ (2013/14-2014/15) في ثلاثة مواقعِ هي محطات بحوث الجزيرة و السوكي والحديبة التابعة لهيئة البحوث الزراعية بالسودان. هدفت الدراسةِ إلي تُقييم هذه التراكيب الوراثية من حيث الانتاجية  ومكوّناتِها و دراسة التفاعل بين البيئة و التراكيب الوراثية المختلفة وتمييز التراكيب الوراثية الأعلى إنتاجية و المستقرةّ في البيئاتِ المختلفة. أوضحت النتائج وجود مدي واسع من التباين الوراثي بين التراكيب الوراثية لمعظم الصفات المدروسة. أيضاً أظهرت النتائج وجود فروقات معنوية كبيرة بين التراكيب الوراثية و البيئة والتفاعل بينهما. أوضحت الدراسة أنه في طريقة الأثر التجميعي الرئيسي والتفاعل المتراكم لتحليل التباين  (AMMI)الناتج عن التفاعل بين التركيب الوراثي والبيئة أن محور المكون الأول والثاني قد  فسرا حوالي 64.6 % و25.3 %، علي التوالي من هذا التباين، بينما وجد في طريقة معامل الارتدادEberhart and Russell’s (1966)  أنه قد فُّسَر حوالي 13.8 % منه. عليه فإن طريقة الأثر التجميعي الرئيسي والتفاعل المتراكم أعلي كفاءةً من طريقة معامل الارتداد الخطي في تقسيم التباين الناتج عن التفاعل بين التراكيب الوراثية والبيئة. خلصت الدراسة إلي أن التراكيب الوراثية Saff 1 و Saff 12و Saff 14 كانت عالية الإنتاجيةً ولها ثباتاً وراثياً في كل بيئات التقييم  لذلك يوصى  بزراعتها بنجاح  تحت ظروف الري الشتوي بأواسط وشمال السودان